2012
DOI: 10.1016/j.ijheatmasstransfer.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A heatline analysis of natural convection in a square inclined enclosure filled with a CuO nanofluid under non-uniform wall heating condition

Abstract: a b s t r a c tHeatline visualization technique is used to understand heat transport path in an inclined non-uniformly heated enclosure filled with water based CuO nanofluid. The cavity has square cross-section and it is nonuniformly heated from a wall and cooled from opposite wall while other walls are adiabatic. The governing equations which are continuity, momentum and energy equations are solved using finite volume method. The dimensionless heatfunction for nanofluid heat flow is defined and solved to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(22 citation statements)
references
References 28 publications
(32 reference statements)
2
20
0
Order By: Relevance
“…As seen, the effects of increasing volume fraction of nanoparticles are more pronounced at lower Rayleigh numbers where conduction heat transfer is dominant. Similar observations were reported by Oztop et al [14] and Abu-Nada and Oztop [20]. Besides, Table 3 (20) These correlations can estimate Nu within average error of 2.6% and maximum error of 5.3%.…”
Section: Natural Convectionsupporting
confidence: 88%
See 2 more Smart Citations
“…As seen, the effects of increasing volume fraction of nanoparticles are more pronounced at lower Rayleigh numbers where conduction heat transfer is dominant. Similar observations were reported by Oztop et al [14] and Abu-Nada and Oztop [20]. Besides, Table 3 (20) These correlations can estimate Nu within average error of 2.6% and maximum error of 5.3%.…”
Section: Natural Convectionsupporting
confidence: 88%
“…Abu-nada and Oztop [20] investigated numerical simulation of natural convection in an inclined cavity filled with Cuwater nanofluid when 10 3 <Ra< 10 5 to report that the effects of increasing nanoparticles volume fraction on heat transfer rate are more pronounced at low Rayleigh numbers similar to Oztop et al. [14]'s findings.…”
Section: Accepted Manuscriptsupporting
confidence: 54%
See 1 more Smart Citation
“…The collective influence of non-uniform nanoparticle diameters, nanoparticles volume fractions, Prandtl number, and Grashof number on the flow and temperature distributions was analyzed exhaustively. In synthesis, it can be attested that natural convective heat transfer in enclosures filled with water can be enhanced by adding nanoparticles of copper, Cu [17][18][19][20], copper oxide CuO [21][22][23], silver Ag [24], alumina Al2O3 [25] and titanium TiO2 [26]. Natural convection heat transfer in closed enclosures having a heated block inside and filled with nanofluids has received considerable attention in recent years due to its practical applications, such as thermal insulation and/or building design.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that heat transfer coefficient increases with increasing Cu nanoparticles concentration. Oztop et al [13] observed the heat transfer coefficient increases by adding CuO nanoparticles concentration in an inclined nonuniformly heated enclosure. On the other hand, Hwang et al [14], Santra et al [15] and Abu-Nada [16] reported a decrease in the heat transfer by increasing the nanoparticles concentration for a particular Rayleigh number.…”
Section: Introductionmentioning
confidence: 99%